The Study about Surface Modification of Steel by Water Plasma - Kong, Jung-Hyun; Takeda, Tomonori; Okumiya, Masahiro; Tsunekawa, Yoshiki; Yoshida, Masashi; Kim, Sang Gweon (International Conference on Plasma Surface Engineering, 2013)
Recently, a lot of research has been carried out to improve the properties of steel surface such as ion-nitriding, gas nitriding. However, they need high vacuum rate or very expensive equipment and longer treatment time. In this study, new nitriding process proposed which have extremely shorter treatment time and very simple equipment by using water plasma. For the water plasma, JIS-SCM420 specimen was used as cathode, and rolled punching stainless steel plate (SUS304) was used as anode. Voltage was applied between electrodes by DC pulsed power supply. Pulsed power supply was used to prevent discharge from concentrating on one point. Urea (H2N)2C=O used as supply source of nitrogen and potassium hydrate (KOH) for adjusting electric conductivity. And it was put into distilled water as electrolyte. Treatment voltage was 600 V, and experiments were conducted by varying conditions such as treatment time and concentration of electrolyte. After water plasma treatment, a lot of fine discharge pores can be seen on the treated steel surface. And also, a few µm modified layer is formed on the steel surface after water plasma treatment within 5min. At the results of XRD analysis, iron nitrides are detected with Fe peaks and the hardness of nitride layer shows about 800HV.